2022
DOI: 10.1111/myc.13467
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiologic outcomes of central nervous system cryptococcosis: Re‐examining the need for a 2‐week cerebrospinal fluid analysis

Abstract: Background Cryptococcus spp. infection involving the central nervous system (CNS) is associated with poor outcomes. Current guidelines recommend repeating a cerebrospinal fluid (CSF) fungal culture after 2 weeks of treatment to evaluate for clearance. However, this practice has not clearly been associated with outcomes. Objectives We sought to assess the relationship between CSF fungal clearance at 2 weeks and 12‐month mortality in patients with CNS cryptococcosis. Methods This is a retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…(2) The relationship between sterile CSF culture and mortality is still controversial. Although rapid clearance of CSF Cryptococcus is associated with a high survival rate, some studies also indicated that high sterile culture rate was not associated with a low survival rate of patients 33,34 and was even associated with high mortality. 35 Notably, AIDS patients had a trend of high 90-day mortality compared with CM patients without predisposing disease and non-AIDS patients with other predisposing disease although no statistical significance was found (log-rank p = .174).…”
Section: F I G U R Ementioning
confidence: 99%
“…(2) The relationship between sterile CSF culture and mortality is still controversial. Although rapid clearance of CSF Cryptococcus is associated with a high survival rate, some studies also indicated that high sterile culture rate was not associated with a low survival rate of patients 33,34 and was even associated with high mortality. 35 Notably, AIDS patients had a trend of high 90-day mortality compared with CM patients without predisposing disease and non-AIDS patients with other predisposing disease although no statistical significance was found (log-rank p = .174).…”
Section: F I G U R Ementioning
confidence: 99%